PERKEMBANGAN EKONOMI KREATIF DALAM MENOPANG PEREKONOMIAN RAKYAT DI MASA PANDEMI COVID 19 (Studi Kualitatif Di 5 Penerbitan Independen) - DJIHADUL MUBAROK; EVA FAUZIANA (Develop: Jurnal Ekonomi Pembangunan, 2021)
The creative economy becomes the major survivor and its growth increased during the COVID19 pandemic. Several sectors in the industry that prioritize creativity and art are increasing in demand. An example is the independent book publishing business, although it is still a micro, small and medium scale business, the business of publishing books through independent channels is increasingly in demand by writers to publish their books in this UMKM scale publisher. On the one hand, readers are also enlivening e-books, aka more and more fond of reading books through online applications. In contrast to the development of this independent publication, several major publishers with retail networks throughout Indonesia were forced to deactivate their outlets during the pandemic, due to the PSBB policy. Therefore, this research focuses on how the creative economy, in this case independent publishing, is able to support the people's economy during the pandemic.